2013
DOI: 10.1080/21641846.2013.843266
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a single bout of exercise on energy and fatigue states: a systematic review and meta-analysis

Abstract: Background: Studies examining acute exercise effects on energy and fatigue levels have not been quantitatively summarized. Purpose: To estimate the population effects of a single bout of exercise on energy and fatigue states and examine potential moderators. Methods: Google Scholar and MEDLINE were searched systematically for published studies that measured changes in energy and fatigue after acute exercise. Meta-analytic techniques were used to analyze 58 energy effects and 58 fatigue effects from the same 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
66
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 74 publications
(61 reference statements)
15
66
0
1
Order By: Relevance
“…The results showed that the majority of a small group of generally healthy pregnant women (i.e., ≥ 77%), on average across 24 workouts, reported increased feelings of energy and reduced feelings of fatigue after a single bout of low-to-moderate intensity muscle strengthening exercise. Generally consistent with studies of non-pregnant samples [4] , increases in energy were somewhat larger (e.g., 8.8 larger VAS change for feelings of physical energy compared to physical fatigue) and more common than decreases in fatigue (e.g., only 3/48 analyses showed nonsignificant pre-to-post exercise changes in energy compared to 8/48 for fatigue).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results showed that the majority of a small group of generally healthy pregnant women (i.e., ≥ 77%), on average across 24 workouts, reported increased feelings of energy and reduced feelings of fatigue after a single bout of low-to-moderate intensity muscle strengthening exercise. Generally consistent with studies of non-pregnant samples [4] , increases in energy were somewhat larger (e.g., 8.8 larger VAS change for feelings of physical energy compared to physical fatigue) and more common than decreases in fatigue (e.g., only 3/48 analyses showed nonsignificant pre-to-post exercise changes in energy compared to 8/48 for fatigue).…”
Section: Discussionsupporting
confidence: 85%
“…Among non-pregnant samples a single bout of exercise, regardless of mode, consistently increases feelings of energy but only decreases feelings of fatigue after 20 minutes or more of low-to-moderate intensity exercise that is accompanied by at least moderate increases in feelings of energy [4] .…”
Section: Introductionmentioning
confidence: 99%
“…and did you feel tired?). Recent research suggests that fatigue items are especially sensitive to high-intensity exercise (Loy, O'Connor, & Dishman, 2013). We speculate that the inclusion of the fatigue items in the SF-36 vitality scale contributed to the greater change in these scores than the POMS-B scores.…”
Section: Discussionmentioning
confidence: 87%
“…Light and moderate, but not vigorous, intensity exercise has previously been reported to reduce fatigue (38). Exercise intensity was coded as light, moderate, or vigorous according to a position stand from the American College of Sports Medicine (19).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, an exacerbation of symptoms after acute exertion is used to diagnose ME/CFS/SEID (11, 17). Fatigue is reduced after standardized (e.g., relative to each individual’s aerobic capacity) low-intensity acute exercise lasting at least 20 minutes in people without ME/CFS/SEID (38). No standardized acute exercise stimulus is used in diagnosis of ME/CFS/SEID, although it is noted that “minimal” activity may provoke symptoms in some people (7, 11).…”
Section: Introductionmentioning
confidence: 99%